Food - Riley, Peter D. (Des Plaines, Ill. : Heinemann Interactive Library, 1998)
Introduces the food cycle and its importance, including how plants manufacture food, the plants, animals, bacteria, and fungi that make up the food cycle, and the fragile balance between feeding the world's human population and preserving the balance of nature.
Includes bibliographical references (p. 30) and index.
L.A. Recommended Foreign Language.
4.8.
4.8
3-6
Keywords: Food chains (Ecology) -- Juvenile literature; Pollution -- Environmental aspects -- Juvenile literature; Ecology; Food chains (Ecology); Ecology; Food chains (Ecology).